Teaching resources in cartographic literacy in elementary school: Possibilities to create and recreate - Araújo, Ione (2023)
In recent years, cartographic literacy has drawn attention within the scope of School Geography. It is noticed limitations on the part of Geography teachers in Cartography teaching, which generates the need of rethinking this teaching method for the formation of students making them capable of reading maps in a meaningful way, beyond the simple and pure decoding (PASSINI, 2009). It is essential that the student not only decode the cartographic signs, but also perceive the concepts and spatialities of what is being observed, in order to make the reading really meaningful (KATUTA, 1997). Faced with difficulties, the geography teacher must creatively seek new teaching practice methodologies. In this context, understanding that teaching becomes way more effective when associated with the insertion of didactic resources. The objective of this paper is to share the experience about the use of didactic resources for the most meaningful teaching of Cartography for  6th grader students of Elementary School at Escola Municipal Odilon Gonzaga Braveza, located in Fortaleza, CE. The use of didactic resources already available and created for a more focused teaching constituted subsidies for a resumption of cartographic studies after the period of remote teaching. Thus, at the end of the semester, the students gathered in the school's multimedia room, where teams were formed with the objective of reinforcing the Cartography subjects seen until then. The results showed an improvement, on the part of the students, in the ability to associate the content taught throughout the semester.